Descriptive analysis on psychomotor development impairments and disabilities in patients attended at Instituto Nacional de Rehabilitacion 2006 - 2008 - Camacho-Conchucos, Herminio Teófilo (2012)
Introduction: Impairment is the direct exteriorization of disease consequences, and disability is restriction or absence of any activity due to impairment. Objectives: To identify impairments and disabilities of psychomotor development and characteristics of patients treated at the Department of Investigation, Teaching and Integral Rehabilitation of Development Disabilities. Design: Observational, descriptive, cross-sectional study. Setting: Instituto Nacional de Rehabilitacion Dra. Adriana Rebaza Flores, Callao, Peru. Participants: Patients treated from 0 to 7 years with definite diagnosis and no evident mental retardation. Interventions: From 5 795 patients attended in the period 2006-2008 we reviewed a sample of 400 medical records, and studied impairments and disabilities and their characteristics. Main outcome measures: Impairments and disabilities of psychomotor development. Results: In the range 0 to 7 years, 76,6% were 0-2 year-old, 51% female, 54,3% from Lima department, 42,8% from Callao province. According to districts of Lima Metropolitana most came from Callao (23,8%) and San Martin de Porres (10,6%). Main diagnoses were specific developmental disorder of motor function (17,5%), mixed specific developmental disorders (15%), cerebral palsy (12%); 91,3% presented some impairment, 66,6% musculoskeletal, 14,5% of the hearing organ, speech 7,9%, psychological 6,8%; 78% reported disability, of locomotion 35,9%, of body disposition 22,8%, of communication 17,6%. As of disability severity 11,9% were severe, 59,3% moderate, 21,2% mild and 7,7% not applicable. Conclusions: In subjects studied main impairments and disabilities were musculoskeletal and locomotion, in patients who were from districts close to the institution, with unsatisfied demand for specialized attention to patients from distant places.